2016
DOI: 10.1016/j.amjmed.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Home Treatment of Pulmonary Embolism in the Era of Novel Oral Anticoagulants

Abstract: Even in the era of novel oral anticoagulants, the vast majority of patients with acute pulmonary embolism were hospitalized, and only a small proportion were discharged in ≤2 days. Although home treatment has been found to be safe in carefully selected patients, and scoring systems have been derived to identify those at low risk of adverse events, home treatment was infrequently selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Treatment of those treated entirely at home was with novel oral anticoagulants in 4 (30.8%) of 13 patients, and in those discharged in 2 days, novel oral anticoagulants were prescribed only for 34 (28.6%) of 119 patients. 32 The oral factor Xa inhibitors rivaroxaban and apixaban were approved for the treatment of deep venous thrombosis and pulmonary embolism by the US Food and Drug Administration on November 2, 2012, and August 21, 2014, respectively. 33,34 Therefore, the impact, if any, of home treatment with these drugs would not be shown in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of those treated entirely at home was with novel oral anticoagulants in 4 (30.8%) of 13 patients, and in those discharged in 2 days, novel oral anticoagulants were prescribed only for 34 (28.6%) of 119 patients. 32 The oral factor Xa inhibitors rivaroxaban and apixaban were approved for the treatment of deep venous thrombosis and pulmonary embolism by the US Food and Drug Administration on November 2, 2012, and August 21, 2014, respectively. 33,34 Therefore, the impact, if any, of home treatment with these drugs would not be shown in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Vinson et al 1 cite a number of previous studies that showed that outpatient pulmonary embolism management is low, 1% to 8%, at centers without defined clinical pathways or realtime clinical decision support. [6][7][8] Our own clinical experience with outpatient management of lower extremity deep venous thrombosis found that nearly all patients were admitted before the adoption of an institutional pathway and monthly compliance audits. 9 The American College of Chest Physicians and the British Thoracic Society, who first recommended outpatient pulmonary embolism management in 2003, advocate outpatient pulmonary embolism management for low-risk patients with adequate social circumstance.…”
Section: Discussion Pointsmentioning
confidence: 99%
“…Unlike Canada and Europe, this is not the current management approach in the United States 23. With an increasing number of risk scoring algorithms developed, we hypothesize that this cost‐saving measure may soon see an increased use in the United States.…”
Section: Methodsmentioning
confidence: 99%